Synthesis, spectral characterization, thermal analysis and DFT computational studies of 2-(1H-indole-3-yl)-5-methyl-1H-benzimidazole and their Cu(II), Zn(II) and Cd(II) complexes - Hadi, Jabbar Saleh; Abdulnabi, Zuhair Ali; Dhumad, Adil Muala (European Journal of Chemistry, 2017)
Cu(II), Zn(II) and Cd(II) metal complexes were obtained by using ligand (2-(1H-indol-3-yl)-5-methyl-1H-benzo[d]imidazole) derived from 4-methyl-1,2-phenelyenediamine and indole-3-carboxaldehyde. The ligand and its metal complexes were characterized by elemental analysis, Mass Spectrometry, FT-IR, 1H NMR, 13C NMR, TG and molar conductance measure-ments. The non-electrolytic behaviour of complexes is confirmed by low molar conductance value. The presence of lattice and coordinated water molecules is confirmed by thermal analysis. Thermodynamic parameters (E, ΔH, ΔS and ΔG) were calculated by using Coats-Redfern method. The density function theory (DFT) calculation at the B3LYP/LanL2DZ method with 6-311+G(d,p) basis set are used to investigate the electronic structure of the ligand and their complexes with Cu(II), Zn(II) and Cd(II) metals. HOMO-LUMO energies of the mentioned compounds have been computed by using DFT/B3LYP calculation method with 6-311+G(d,p) basis set and LanL2DZ basis set for Cu(II), Zn(II) and Cd(II) metal complexes. Mulliken charge distributions of the investigated compounds were also computed with same level of method.